2014
DOI: 10.1007/s00784-013-1178-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress is responsible for genotoxicity of camphorquinone in primary human gingival fibroblasts

Abstract: A more detailed insight into genotoxic mechanisms in oral cells can be of great importance for a better understanding of the biocompatibility of CQ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Recently, we reported that CQ caused DNA damage in association with an increased ROS generation in primary human gingival fibroblasts [13]. Furthermore, we documented that this damage was in part of oxidative nature [40]. These findings are supported by our present study, which shows an increase of tail moment for CQ concentrations of 2.5 mM and higher.…”
Section: Okf6/tert2 Cellssupporting
confidence: 90%
See 1 more Smart Citation
“…Recently, we reported that CQ caused DNA damage in association with an increased ROS generation in primary human gingival fibroblasts [13]. Furthermore, we documented that this damage was in part of oxidative nature [40]. These findings are supported by our present study, which shows an increase of tail moment for CQ concentrations of 2.5 mM and higher.…”
Section: Okf6/tert2 Cellssupporting
confidence: 90%
“…Former studies show a genotoxic potential already at lower milimolar concentrations of CQ in cultures of human gingival fibroblasts [13,40]. Therefore OKF6/TERT2 (as first target cells) may have very efficient and fast repair mechanisms and/or more effective oxidative defense mechanisms thus preventing DNA damage due to higher ROS levels.…”
Section: Cq (A Paired T-test) and Cells Treated With 2mm Cq + Homentioning
confidence: 99%
“…It is conceivable that incorporation of hydrophilic photoinitiators in resin will allow photoinitiators to diffuse more freely within the hydrophilic-rich phases in higher concentrations. Current dentin adhesives should be optimized to include an adequate concentration of efficient hydrophilic photoinitiators, but it must also be considered that photoinitiators in high concentration could elicit cytotoxic effect (Wessels et al 2014). Ongoing research is exploring novel, efficient hydrophilic photoinitiators that will be compatible with resin/water in the oral cavity and capable of imparting optimal polymerization to the hydrophilic-rich phase.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, camphorquinone increased DNA damage in primary human gingival fibroblasts at all concentrations as a result of intracellular oxidative stress and subsequent down-regulation of glutathione level (52,53).…”
Section: Dental Restorative Materials and Related Compoundsmentioning
confidence: 95%